One Stop Services in Docking Ships at Tanjung Perak Port Surabaya - Jumriani Jumriani; Rosliawati Rosliawati (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2022)
The purpose of this study was to determine the accuracy of One Stop Service (OSS) in ships berthing at the port of Tanjung Perak, Surabaya. This research was conducted for one year starting from March 2020 to October 2020. This study used mix method (qualitative dan quantitave) with the source of the data obtained was primary data obtained directly from the research site by means of interviews and literature related to the title research result. The results obtained from this study indicate that the obstacles that occur in One Stop Service Center services in ships berthing at the port of Tanjung Perak are caused by a lack of pilots and pilot boats to guide ships to the port of Tanjung Perak, Surabaya. Based on data on the list of ships berthed at the Port of Tanjung Perak, Surabaya, of the 40 berths there were 34 (85%) ships that experienced delays in berthing while there were 6 ships that experienced punctual berthing (15%). It can be concluded that the ship berthing One Stop Service model has been carried out well in order to produce good goods documents and must add guide ships to improve smooth ship berthing services at PT. Port of Indonesia III, Tanjung Perak, Surabaya.